Extracorporeal methods of blood glutamate scavenging: a novel therapeutic modality. (May 2015) - Zhumadilov, Agzam; Boyko, Matthew; Gruenbaum, Shaun E; Brotfain, Evgeny; Bilotta, Federico; Zlotnik, Alexander
Abstract : Pathologically elevated glutamate concentrations in the brain's extracellular fluid are associated with several acute and chronic brain insults. Studies have demonstrated that by decreasing the concentration of glutamate in the blood, thereby increasing the concentration gradient between the brain and the blood, the rate of brain-to-blood glutamate efflux can be increased. Blood glutamate scavengers, pyruvate and oxaloacetate have shown great promise in providing neuroprotection in many animal models of acute brain insults. However, glutamate scavengers' potential systemic toxicity, side effects and pharmacokinetic properties may limit their use in clinical practice. In contrast, extracorporeal methods of blood glutamate reduction, in which glutamate is filtered from the blood and eliminated, may be an advantageous adjunct in treating acute brain insults. Here, we review the current evidence for the glutamate-lowering effects of hemodialysis, peritoneal dialysis and hemofiltration. The evidence reviewed here highlights the need for clinical trials.